Peluang dan Tantangan Pendidikan Agama Islam dalam Membentuk Karakter Religius Siswa di SMPN Cipendeuy Bandung Barat - Ari Abdul Kohar Rahmatullah; Sigit Ardiguna; Rizka Ratih; Aris Munandar (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
This research is motivated by the importance of Islamic Religious Education (PAI) in shaping the religious character of students at the junior high school level, particularly at SMP Cipeundeuy. However, its effectiveness is often hampered by the lack of parental involvement in accompanying and providing religious role models at home. This lack of parental participation results in low motivation and understanding of students toward PAI, thus requiring better synergy between school and family to improve learning outcomes and the formation of students’ religious character. The aim of this study is to identify the opportunities and challenges of PAI in shaping students’ religious character, as well as to analyze the roles of teachers and the school environment in supporting this process. A descriptive qualitative approach was used. Data were collected through in-depth interviews with PAI teachers and students, observation of the learning process and religious activities at school, as well as documentation of the curriculum and character development programs. Data analysis was conducted using reduction, presentation, and verification techniques to obtain a comprehensive picture of PAI implementation at SMP Cipeundeuy..The results indicate that relevant PAI materials and varied learning methods are significant opportunities for shaping students’ religious character. However, there are still challenges such as limited time, social environmental influences, and varying student motivation. Optimizing PAI learning and synergy between school, teachers, and the environment is expected to enhance the effectiveness of religious character formation among students at SMP Cipeundeuy.